Morphological effect of different superovulation protocols to the mouse ovary - Başar, Murat; Türker, Mehmet; İrez, Tülay; Arda, Oktay (Cerrahpaşa Medical Journal, 2019)
Objectives: The objective of this study was to evaluate the effects of GnRHa on; ovarian morphology, oocyte diameter, number and maturation of oocytes in superovulated mice with FSH and hCG. Methods: Three month old BALB/C female mice (weight: 25-30 g) were assigned to 3 experimental groups, which were: control, superovulated and superovulated with GnRHa pretreatment (n=10 per group). Control mice had an i.p. injection of 0.1 ml 0.9% NaCl. Results: Superovulation induced with 5 IU FSH (i.p.) and 5 IU hCG (i.p.) 48 hours later. Mice in the superovulated with GnRHa pretreatment group received GnRHa (20 mg/kg) 24 hours before superovulation. Mice were sacrifice by cervical dislocation thirteen hours after hCG administration. The ovaries and oviducts harvested for histological assessment. Conclusion: The oocyte numbers and their maturation, ovulation rate, and the diameters of the oocytes were higher in GnRHa pretreated group than the control and superovulated ones (p<0.001). In conclusion, the GnRHa administration increased the number and the maturation of oocytes and the rate of ovulation in mice. Additionally, we concluded that as an oocyte assessment criteria evaluation of oocyte diameters in IVF procedure is an useful tool and better embryo for successful pregnancy.